Pengenalan Usaha Affiliate Marketing Pada Platform Shoope Terhadap Mahasiswa Universitas Muhammadiyah Palopo - Magfirah Indah R; Kiki Fatmawati; Astrid Astrid; Nanda Nanda; Suraidah Suraidah (CV. ITTC INDONESIA, 2025)
The development of digital technology has brought major changes in e-commerce, including marketing strategies through affiliate marketing. Shopee, one of the leading e-commerce platforms, is the main choice of MSMEs in Indonesia for online transactions. This article discusses the introduction of affiliate marketing through the Shopee platform to students of Universitas Muhammadiyah Palopo. Using the PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize) method, this research explains the process of preparation to optimization in running effective affiliate marketing. Gen Z generation, as a group familiar with technology and social media, has great potential to manage digital marketing strategies. The Shopee Affiliate program offers additional income opportunities through online product promotion. With a systematic approach, this program not only helps Gen Z understand affiliate marketing, but also encourages their creativity and entrepreneurial opportunities. This article is expected to be a foundation in digital business development for the younger generation in the technological era.